Fitness-related differences in the rate of whole-body evaporative heat loss in exercising men are heat-load dependent - Lamarche, D. T.; Notley, S. R.; Louie, J. C.; Poirier, M. P.; Kenny, G. P. (Experimental Physiology, 2018)
What is the central question of this study?